Glycated Hemoglobin as A Marker for Predicting Outcomes of Patients with Hemorrhagic Stroke - Khan, Moid; Badshah, Mazhar; Hussain, Ahmed; Khan, Najeeb; Khan, Faiz; Tariq, Nabeel (Indus Journal of Bioscience Research, 2025)
Background: A severe cerebrovascular event with a high morbidity and fatality rate is hemorrhagic stroke (HS). Finding trustworthy prognostic indicators is essential to enhancing clinical results. Glycated hemoglobin (HbA1c), which has been connected to vascular dysfunction and the risk of stroke, is a measure of long-term glycemic management. Its predictive usefulness for hemorrhagic stroke outcomes is still unknown, though. Objective: This study aims to evaluate the role of HbA1c as a predictive biomarker for clinical outcomes in patients with hemorrhagic stroke, focusing on stroke severity, functional recovery, and mortality. Methods: At Quetta's Bolan Medical Complex Hospital, 300 patients with hemorrhagic stroke were the subjects of a prospective observational study. Based on their HbA1c readings, patients were divided into three groups: <5.7%, 5.7%–6.4%, and >6.5%. The Glasgow Coma Scale (GCS) and NIH Stroke Scale (NIHSS) were used to measure clinical severity. The modified Rankin Scale (mRS) was used to assess functional outcomes both at discharge and ninety days after the stroke. Independent predictors of unfavorable outcomes were found using logistic regression analysis. Results: Significantly negative outcomes were seen by patients with HbA1c >6.5%, including higher mean blood pressure (160/95 mmHg ± 14, p=0.001), higher NIHSS scores (14.7 ± 5.2, p=0.002), and lower GCS scores (8.9 ± 3.2, p=0.001). This group had the lowest functional independence (18.2%, p=0.001) and the highest mortality (36.4%, p=0.002). Along with age >60 years, hypertension, and high NIHSS scores, logistic regression verified that HbA1c >6.5% was an independent predictor of poor functional recovery (OR: 2.9, p=0.001). Conclusion: In hemorrhagic stroke patients, elevated HbA1c levels are linked to worse functional recovery, higher mortality, and more severe stroke. A major independent predictor of unfavorable outcomes is a HbA1c >6.5%. These results imply that regular HbA1c testing could help patients with hemorrhagic stroke with risk assessment and clinical decision-making.